Auxiliar nos desafios dos modelos de negócios para sustentabilidade em startups : ferramenta Mix Tool for Sustainability - Nunes, Andressa Kelly da Silva (2023)
Business Models for Sustainability stand out for their ability to structure businesses along more sustainable paths. One of the ways to help sustainable entrepreneurship is through the tools of business models for sustainability. The application of these tools can be combined in such a way that they cover the needs of startups. In order to contribute to this research topic, the general objective of this dissertation is to propose a tool for diagnosing and analyzing the challenges of business models for sustainability in the context of startups. The study identifies aspects of sustainable value tool approaches within the context of business models. By analyzing the literature and the positive and negative points of the pilot application of a business model tool for sustainability, it was possible to propose a new tool, the Mix Tool for Sustainability. It was applied to five startups through workshops. As a way of analyzing the application of the proposed tool, the perceptions of the workshop participants were surveyed. The workshop allowed the startups to discuss their value proposition, stakeholder engagement, challenges faced and prioritize actions to overcome the challenges identified. The application of the tool was positively perceived by the workshop participants, indicating its positive contribution to these organizations. Future studies could verify its contribution to startups in other locations, as well as identifying opportunities for improvement in the application of the proposed tool.